DOP071 Tight control with adalimumab-based treatment is associated with improved quality of life outcomes in patients with moderate to severely active Crohn's disease: data from CALM. (16th January 2018) - Panaccione, R; Colombel, J -F; Bossuyt, P; Baert, F; Vanasek, T; Danalioglu, A; Novacek, G; Armuzzi, A; Reinisch, W; Neimark, E; Petersson, J; Robinson, A M; et al.
Abstract: Background: The Phase 3 CALM study demonstrated that tight control (TC) of inflammation based on biomarkers led to superior clinical outcomes including endoscopic and deep remission in patients with moderate to severe Crohn's disease (CD) compared with standard clinical management (CM). 1 Quality of life outcomes were analysed in this study. Methods: Adult patients who were immunomodulator and biologic-naïve with active CD were treated with a prednisone burst and taper for ≤8 weeks, and randomised 1:1 to TC or CM at week 0. Patients received up to four treatment options (TOs) administered in a stepwise manner based on pre-defined success criteria: TO1=no treatment; TO2=160/80 mg adalimumab (ADA) weeks 0/2, then 40 mg every other week; TO3=ADA 40 mg weekly; TO4=ADA 40 mg weekly + azathioprine 2.5 mg/kg/day. The following outcomes and the values change from baseline (BL) were assessed at weeks 12, 24, 36 and 48: Inflammatory Bowel Disease Questionnaire (IBDQ), SF-36 Physical Component Summary Score (SF-36 PCS) and Mental Summary Score (SF-36 MCS), Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F), Patient Health Questionnaire-9 (PHQ-9) and Work Productivity and Activity Impairment (WPAI) questionnaire. IBDQ response (∆IBDQ≥16 from BL) and remission (IBDQ>170) were assessed at weeks 12, 24, 36 and 48. Mixed models were used to estimate the difference in improvement (i.e., change from BL) between TC and CM over 48 weeks and at each visit; logistic regression was used to assess IBDQ response/remission. Results: In total, 244 patients were randomised. BL characteristics and outcome values were similar between groups. At week 48, significantly more patients in TC vs. CM had an IBDQ response and were in IBDQ remission (Table 1). Over the course of the study, average improvement (outcome values change from BL) were significantly greater in TC vs. CM for IBDQ, SF-36 PCS, SF-36 MCS, FACIT-F, PHQ-9 and daily activity impairment; and was numerically greater for work time missed, impairment while working, and overall work impairment (Table 2). Conclusions: Compared with CM, TC with an ADA-based strategy was associated with normalisation of CD symptoms as well as significant improvement in general and disease-specific quality of life, fatigue and depression. Reference: 1. Colombel, et al. Lancet 2017.